Exosomes in arteriovenous fistula stenosis - Cao, Yushi; Guo, Fangxiao; Chen, Dandan; Li, Lei; Jie, Xiangyu; Wang, Weitie (Frontiers in Cell and Developmental Biology, 2025)
Arteriovenous fistula (AVF) stenosis is a complex pathological process caused by venous intimal hyperplasia, and its development is influenced by factors such as surgical injury, hemodynamic changes, inflammatory responses, and cellular proliferation and migration. Exosomes are critical mediators of intercellular communication and carry biomolecules (e.g., deoxyribonucleic acid, ribonucleic acid [RNA], and proteins) that can regulate cell functions and impact inflammatory responses, endothelial cell proliferation, and vascular smooth muscle cell migration. Studies have shown that molecules such as microRNAs within exosomes play significant roles in vascular stenosis-related diseases and can function as potential therapeutic tools and biomarkers for disease diagnosis. In addition, exosomes can serve as drug carriers with good biocompatibility and targeting capabilities, providing new avenues for the diagnosis and treatment of AVF stenosis. This article reviews the application of exosomes in AVF stenosis.